2012
DOI: 10.1080/17408989.2011.565471
|View full text |Cite
|
Sign up to set email alerts
|

The focus, role, and meaning of experienced teachers' reflection in physical education

Abstract: Background: It has been widely accepted that reflective teaching is a powerful component of effective teaching. Accordingly, educating reflective practitioners has been a major goal of teacher education. Reflective teaching refers to the act of thinking such as analyzing or assessing educational meanings, intentions, beliefs, decisions, actions, or products yielded through those thinking processes. Reflective practitioners are those who contemplate and negotiate the complexities of teaching to enhance their de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 26 publications
0
22
0
31
Order By: Relevance
“…Reflection is understood as a process that encourages practitioners to evaluate their goals, actions and the implications these have on the students they teach (Elliott, 2005;Ermeling, 2012;Jung, 2012;Leitch & Day, 2000;Pedro, 2005). Furthermore, reflection facilitates the acknowledgement and understanding of how the context and 'site expectations' influence their pedagogy (Casey, 2012a;Elliott, 2005;Leitch & Day, Asia-Pacific Journal of Health, Sport and Physical Education 21 2000).…”
Section: Practitioner Inquirymentioning
confidence: 95%
“…Reflection is understood as a process that encourages practitioners to evaluate their goals, actions and the implications these have on the students they teach (Elliott, 2005;Ermeling, 2012;Jung, 2012;Leitch & Day, 2000;Pedro, 2005). Furthermore, reflection facilitates the acknowledgement and understanding of how the context and 'site expectations' influence their pedagogy (Casey, 2012a;Elliott, 2005;Leitch & Day, Asia-Pacific Journal of Health, Sport and Physical Education 21 2000).…”
Section: Practitioner Inquirymentioning
confidence: 95%
“…Physical education research on reflection has mainly focused on the pre-service level, with the exception of few studies (e.g. Jung, 2012; Tsangaridou and O’Sullivan, 1997). Some studies have described how specific courses were designed to enhance reflective abilities among the prospective teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Educational researchers have shown the significance of understanding reflection across teachers with a range of experiential levels: José Chamoso, María Cáceres, and Pilar Azcárate (2012) examined reflection to show the challenges pre-service teachers faced in developing an identity as an 'authentic' [mathematics] teacher; Edward Pultorak (1993) constructed a set of questions that enabled novice teachers to reflect more comprehensively on their practice; and Jinhong Jung (2012) showed that properly structured reflection employed by experienced teachers can help them with (a) making sense of unforeseen events, (b) developing knowledge-in-action, (c) making on-the-spot decisions, and (d) reconstructing their belief systems (p. 157). Recently, the centrality of reflection to improving teaching and learning in K-12 schools has even been tied to the development of teacher leaders.…”
Section: Resultsmentioning
confidence: 99%